FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT INVESTOR PEMULA UNTUK BERINVESTASI DI PASAR MODAL PADA MASA PANDEMI COVID-19 - Iqbal Driantama; Kartika Kartika; Oktaviani Ari Wardhaningrum (Universitas Negeri Padang, 2022)
Investments in the capital market are starting to be in demand, especially during the COVID-19 pandemic. This is evidenced by the increasing number of investors due to the fact that during the COVID-19 pandemic, people have a desire to make profits in the midst of demands to reduce activities outside the home. This study aims to determine the effect of perceived returns, perceived risk, knowledge, and technological progress on the investment interest of novice investors at the Faculty of Economics and Business, University of Jember during the covid-19 pandemic. This type of research is quantitative research. The population of this research is the students of the Faculty of Economics and Business, University of Jember who are active in the 2021/2022 academic year. The sampling technique used purposive sampling technique with data collection techniques using a questionnaire. The data obtained from the distribution of the questionnaire is 100 data. The research method used is multiple linear regression analysis. The results of hypothesis testing using the T test prove that the perceived returns, risk perceptions, knowledge, and technological advances have a significant positive effect on the interest of novice investors to invest in the capital market during the COVID-19 pandemic.Keywords: Investment Interest, Perception of Return, Perception of Risk, Knowledge, Technological Advancement